Harmonization of Criminal Sanctions against Notaries: A Comparative Analysis between Indonesian Positive Law and the Concept of Jarimah Takzir in Islamic Law - Yanuardi Amin; Ruslan Ruslan; Ramlah Ramlah; Rida Luthfiana Wakhidah Wakhidah; Ashraf Jomah Mohammed Milad (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
The notarial profession in Indonesia occupies a strategic position as a public official authorized to create authentic deeds with complete evidentiary force; however, the phenomenon of notarial involvement in criminal acts has experienced a significant increase that threatens professional integrity and public trust in the notarial institution. At least 137 notaries have been implicated in criminal cases, with the majority involving document forgery, fraud, and embezzlement, while the regulation of criminal sanctions in Law Number 2 of 2014 concerning Notarial Positions remains limitative and creates legal uncertainty. This research aims to comprehensively analyze the legal implications of imposing sanctions on notaries who commit criminal acts by integrating perspectives from positive law and Islamic law, identifying juridical and non-juridical factors causing notaries to receive criminal sanctions, analyzing the harmonization of supervision systems and sanction imposition mechanisms, and examining the concept of jarimah takzir as an educative and rehabilitative alternative to punishment. The research employs a normative juridical method with statutory and conceptual approaches, analyzing primary legal materials consisting of legislation and court decisions, secondary legal materials comprising scholarly literature, and tertiary legal materials, through library research techniques and qualitative data analysis using descriptive-analytical methods and deductive reasoning. The research findings indicate that juridical factors in the form of normative vacuums in criminal sanctions and non-juridical factors in the form of moral integrity degradation constitute the primary determinants; the supervision system necessitates coherent harmonization among administrative, civil, ethical code, and criminal sanctions by applying the principle of ultimum remedium, while the Islamic law perspective through the concept of jarimah takzir offers a philosophical alternative emphasizing educative and rehabilitative dimensions by classifying deed forgery as a manifestation of falsehood and breach of trust that contradicts Islamic principles of justice. This research contributes theoretically to strengthening the theory of criminal liability for official positions and practically recommends legislative reformulation to fill legal vacuums and strengthen a supervision system that is rigorous yet just in order to maintain the integrity of the notarial profession and the legitimacy of public trust in the notarial institution within the framework of Indonesia's national legal system